The use of anakinra in a patient with gout and long-term follow-up of rheumatoid arthritis - E. V. Cheremushkina; M. S. Eliseev; A. S. Semashko; A. V. Alekseeva; A. M. Lila (Современная ревматология, 2023)
Gout is a chronic inflammatory arthropathy, caused by articular and periarticular sodium monourate (MUN) crystals deposition on the background of chronic hyperuricemia. Gout belongs to the group of autoinflammatory diseases characterized by activation of the innate immune system. In some cases, especially in women, with a long course of the disease and absence of adequate therapy, chronic arthritis is detected, which has little difference from that in rheumatoid arthritis (RA). At the same time, until recently, the combination of RA and gout was considered casuistry due to the inhibition of crystal formation by specific factors associated with RA, what is more mechanisms of inflammation development characteristic of these diseases are completely different. However, according to the latest data, the coexistence of these two diseases in one patient is possible, and the therapy of both, gout and RA (in some patients) can be successful when prescribing biological disease modifying antirheumatic drugs, in particular inhibitors of the interleukin 1 receptor (IL1r).The article presents a rare clinical case of chronic tophi gout in an elderly patient who was followed up for a long time with a diagnosis of RA, a significant improvement was achieved on therapy with the IL1r antagonist anakinra.